TIP5;1 is an aquaporin specifically targeted to pollen mitochondria and is probably involved in nitrogen remobilization in Arabidopsis thaliana - Soto, Gabriela Cynthia (2010)
In plant sexual reproduction, water and solute movement are tightly regulated, suggesting the involvement of aquaporins. We previously identified TIP5;1 and TIP1;3 as the only Arabidopsis aquaporin genes that are selectively and highly expressed in mature pollen, and showed that they can transport both water and urea when expressed in Xenopus oocytes. Here, we show that TIP5;1 has unusual characteristics, as its water transport activity is regulated by pH. Analysis of the water transport activity of a mutant version of TIP5;1 (TIP5;1-H131A) and amino acid alignment with other plant aquaporins regulated by pH suggested that a conserved motif is involved in pH sensing. GFP–TIP5;1 is located in the mitochondria of pollen tubes. The single mutants tip1;3 and tip5;1, as well as the tip1;3 tip5;1 double mutant, are fertile, but all mutants had shorter than normal pollen tubes when germinated in vitro in the absence of exogenous nitrogen. Thus, we propose that TIP5;1 and TIP1;3 are involved in nitrogen recycling in pollen tubes of Arabidopsis thaliana.